Maternal Knowledge Levels on Nutrition in Toddlers: An Overview - Firmansyah, Bevaldi; Rahman, Irpan Ali; Marliany, Heni (Inspirasi Foundation, 2024)
Introduction: Maternal knowledge about nutrition plays a crucial role in ensuring optimal growth and development of toddlers during their critical early years. Understanding the variations in maternal knowledge levels can provide valuable insights into nutritional practices and their impact on child health outcomes. Objective: The objective of this article is to analyze and describe the levels of maternal knowledge regarding nutrition in toddlers to identify gaps and inform strategies for improving child health outcomes. Methods: This study employed a cross-sectional design to assess maternal knowledge of toddler nutrition. The population included mothers with children aged 12–59 months, with a sample of 36 participants selected through accidental sampling. The research was conducted in Wado, Sumedang Regency, from April 25 to May 25, 2024. Data were analyzed using frequency and percentage calculations, facilitated by SPSS software version 22. Results: The study results showed that the majority of mothers had good knowledge about providing nutrition for toddlers, with 33 participants (86%) categorized as good, while the remaining 3 participants (14%) had moderate knowledge. Conclusions: The study concludes that most mothers have good knowledge of toddler nutrition, indicating positive awareness within the community. However, the presence of a small proportion with moderate knowledge highlights the need for targeted educational interventions. Health practitioners should develop tailored nutrition education programs to address these gaps and enhance maternal capacity to support optimal child growth and development.